2018
DOI: 10.3390/mi9050206
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Carrier-Aided Thin Film Electrode Array Design for Cochlear Insertion

Abstract: The micro-fabricated thin film electrode array (TFEA) has been a promising design for cochlear implants (CIs) because of its cost-effectiveness and fabrication precision. The latest polymer-based cochlear TFEAs have faced difficulties for cochlear insertion due to the lack of structural stiffness. To stiffen the TFEA, dissolvable stiffening materials, TFEAs with different structures, and TFEAs with commercial CIs as carriers have been invested. In this work, the concept of enhancing a Parylene TFEA with Kapton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…To stiffen Parylene-C electrode arrays, Kapton tape was used as an electrode array carrier material for long-term implants. The incorporation of Kapton tape increased the bending stiffness of the Parylene-C array by 60% [ 90 ]. In addition to stiffness, the size of electrode arrays affects the flexibility of the implant [ 91 ].…”
Section: Electrode and Electrode Array Designmentioning
confidence: 99%
“…To stiffen Parylene-C electrode arrays, Kapton tape was used as an electrode array carrier material for long-term implants. The incorporation of Kapton tape increased the bending stiffness of the Parylene-C array by 60% [ 90 ]. In addition to stiffness, the size of electrode arrays affects the flexibility of the implant [ 91 ].…”
Section: Electrode and Electrode Array Designmentioning
confidence: 99%
“…It was shown that parylene-based implants are robust under surgical conditions and deliver efficient stimulation in in vivo testing ( 140 , 161 163 ). Parylene is used as both substrate and insulating material for cochlear implants and cortical stimulation ( 141 , 164 ). Minnikanti et al ( 165 ) performed a comprehensive study to examine parylene C long-term stability, demonstrating that Al 2 O 3 coating significantly enhances insulation properties and improves lifetime of neural interfaces for chronic implantation ( 166 ).…”
Section: Flexible Substratesmentioning
confidence: 99%
“…Two flexible arrays developed for measuring pressure [6] or providing electrical signals to cochlear implants [7] are reported. In the case of cochlear implants, Parylene-C again is the polymer of choice, but in this work it is reinforced with Kapton to aid in insertion of sensors into tissues.…”
mentioning
confidence: 99%